Research hotspots and trends of post-stroke depression rehabilitation: a bibliometric analysis from 2003 to 2024 - Cai, Hongwei; Cai, Shini; Li, Aihong; Guo, Aisong (Frontiers in Neurology, 2025)
BackgroundPost-stroke depression (PSD) is a common complication of stroke and is associated with stroke prognosis. Rehabilitation plays an essential role in the comprehensive treatment of PSD. However, there are few bibliometric analyses of studies on PSD rehabilitation. This study aimed to comprehensively sort out the network of PSD rehabilitation through bibliometric analyses, analyze the research trends, focus on the hotspots related to PSD rehabilitation, and provide new research perspectives and guidance for future studies.MethodsThe Web of Science Core Collection (WoSCC) database was searched for studies about depression rehabilitation after a stroke. The search covered the period from January 1, 2003, to October 31, 2024. We analyzed countries, institutions, journals, authors and keywords using CiteSpace and VOSviewer software to create visualizations and perform a bibliometric analysis.ResultsA total of 2,227 papers were analyzed, with an increasing trend in the number of papers published each year. The United States had the highest number of published articles (458 publications), and Maastricht University and Utrecht University were the most published institutions (56 articles). Archives of Physical Medicine and Rehabilitation is the journal with the most cited publications (5,913 citations). Johanna M. A. is the most prolific author (24 publications).ConclusionUsing bibliometric methods, relevant studies on PSD rehabilitation were reviewed. The hotspots of future research on PSD rehabilitation will center on the brain plasticity mechanism of PSD rehabilitation, PSD assessment, and new techniques of PSD rehabilitation. This article provides systematic information to support and guide future research in this area.